Otimização de rotas num sistema de Bike-Sharing usando sinais fisiológicos - Damien Guedes da Rosa (2015)
Over the years, the bike-sharing has received a widespread attention due to initiatives to increase the use of bicycles instead of motorized transports. The objective of this change is to minimize the use of urban transport that release greenhouse gases which causes environmental problems and traffic congestion. Take in account the alternative to urban transport and motor vehicles, in order to adopt a green and healthy lifestyle, many cities around the world attempts to provide this lifestyle to its citizens, building bike-sharing systems and making available parking spaces for bicycles.In this paper, we intended to show the creation of a system which with the measurement of physical parameters, through physiological sensors and Wearable devices, may advise about the more optimized routes for the users and how the bike-sharing system can be linked with other public transports. In the end of this thesis, we expect an Android application, called SmartBikeEmotion, which aims to allow the users take advantages of the bike-sharing system, with the strength of the circuits adaption to the user's physical condition, assisting them in the cycling through the city. This application will be integrated with BikeEmotion project, a bike-sharing project, developed in partnership by Ubiwhere, Ponto.C, Micro I / O, and University of Aveiro.